PTU-032 Endoscopic stenting – a five year retrospective study. (17th June 2017) - Johnston, T; Matull, R
Abstract : Introduction: Oesophageal, duodenal, gastric (UGI) and colorectal stenting are procedures performed every week in Musgrove Park Hospital Taunton, (a 700 bed District General Hospital in the Southwest of England). Division of labour betweeen Gastroenterology, Radiology and Surgical Teams. Most stenting performed for palliative symptom relief in malignant obstruction and a small proportion of cases are for benign peptic stricturing. We examined our current practice including patient symptoms, morbidity and mortality. Established standards not well defined in this area and so compared our outcomes against our historic practice and against other centres. Method: Retrospective analysis of procedures between June 2011 and June 2016 and survival up until November 2016. 289 recorded cases over this period (a representative sample of cases cases performed). These detailed both colorectal stenting and UGI stenting. Data taken from endoscopy records, patient's letters, MDT outcomes and the Somerset Cancer Register.. 30 day mortality, 8 day readmission rates, survival post stent and designation of the endoscopist or operator in this cohort examined. In subcohort of 159 cases (cases from November 2013 until June 2016) patient's pain score post procedure as well and dysphagia scores pre and post procedure (within the upper gastro-intestinal stenting cohort) examined. Select cohort chosen because previously patients symptoms not consistently recorded. Dysphagia score was derived from the National Oesophago-gastric Cancer Audit. Pain score was classified numerically 0 (no pain) - 3 (breakthrough pain despite opiates. Results: Key findings (all cases): Survival range 0–1219 days Mean age of patient 73 Male 203, Female 86 30 day mortality - 23% (excluding benign cases) 8 day readmission rate: 5.9% (11.9% if including those remaining in hospital for ongoing care) Procedures performed:- Oesophageal (including gastro-oesophageal): 176 Stomach: 3 Duodenal (including gastric pylorus): 40 Colorectal: 70 Patient Symptoms (Upper GI):- - Any dysphagia at one month 42% (96% pre stent), mean dysphagia score 0.85 (2.86 pre stent) - Any dysphagia at 3 months 39%, mean dysphagia score 0.39 - Mean pain score pre stent 0.58, 0.46 one month post stent. Patient symptoms (Colorectal):- - Mean pain score 1.03 pre stent to 0.11 one month post stent. Specific Mortality Data:- Oesophageal: 30 day mortality 20.1% Mean survival 135 days Duodenal: 30 day mortality 17.1% Mean survival 147 days Colorectal 30 day mortality 20.0% Mean survival 239 days Complication and failure rates:- Failure of procedure: 14.4%, Minor Complication:1.9% Serious Complications: 3.1% (Of which 2.5% could have contributed to death) Conclusion: UGI stenting leads to improvement in dysphagia but no change in pain score. Lower GI stenting leads to gross improvement in pain score. Our survival data is comparable to similar published data although our average age of patient is higher than comparable studies. Disclosure of Interest: None Declared